Green synthesis of silver and iron nano composites using aqueous extract of zanthoxylum armatum seeds and their application for removal of acid black 234 dye - Bashir, Nadia; Gulzar, Saba; Shad, Salma (Frontiers in Toxicology, 2024)
Green nanotechnology has gained attraction in recent years due to the growing awareness of the environmental and health risks associated with traditional methods of nanomaterial synthesis. In the present study, nanocomposite (NCs) of silver and Iron were prepared using Zanthoxylum Armatum seeds aqueous extract which acts as a reducing, stabilizing, and capping agent. The synthesized NCs were characterized using UV/Vis Spectroscopy, powder X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and EDX. The UV/Vis spectroscopy analysis of the NCs revealed the presence of a surface plasmonic resonance band occurring at 420 nm. Examination of the NCs through SEM demonstrated that they exhibited a nearly spherical morphology, with an average particle diameter measuring 54.8 nm. The crystalline nature of these NCs was verified through X-ray diffraction (XRD), and the calculation of crystallite size using the Scherrer-Debye equation yielded a value of 12.6 nm. The adsorption ability of newly synthesized nanocomposites was investigated against Acid Black 234 Dye. The results showed that a 0.5 g of NCs dose at pH 4 removed 99.3% of 10 mg/L of Acid Black 234 Dye within 60 min. Based on the findings of this research, it can be inferred that the that Ag-Fe NCs synthesized from Zanthoxylum Armatum seeds aqueous extract hold significant potential for addressing environmental pollution caused by Acid Black 234 Dye. The NCs were used as adsorbent for the removal of Acid Black 234 dye from the wastewater sample and showed 98% removal of dye from the commercial sample within 60 min. In this context, the research highlights that the environmentally friendly synthesis of Ag-Fe nanocrystals (Ag-Fe NCs) using Zanthoxylum Armatum as a mediator offers an efficient and cost-effective solution for mitigating environmental pollution.